2018
DOI: 10.12659/msm.906274
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Adipose Tissue Fatty Acid Composition in Men with Uronephrolithiasis and Metabolic Syndrome

Abstract: BackgroundFatty acids (FA) and their metabolites are closely related to some mechanisms involved in the development of uronephrolithiasis. The aim of this study was to evaluate the relationship between FA composition and type of kidney stones.Material/MethodsAbdominal adipose tissue fatty acid methyl esters of 71 men with nephrolithiasis were identified by GC/MS, and the type of kidney stones was identified using FTIR infrared spectroscopy. Patients were divided into groups according to diagnosis of metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Esterified fatty acids in glycerophospholipids are potential precursor for lipid mediators, especially ω-3 fatty acids ( Kang, 2012 ; Hishikawa et al, 2017 ). The concentration of ω-3 fatty acids in glycerophospholipids was obviously elevated in EEOS group mice than in model group, which is consistent with found that ω-3 fatty acids were significantly upper in normal people compared to patients with uronephrolithiasis ( Bikulčienė et al, 2018 ), indicating that EEOS extract may reduce the occurrence of kidney stones by regulating the ω-3 fatty acids metabolism.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Esterified fatty acids in glycerophospholipids are potential precursor for lipid mediators, especially ω-3 fatty acids ( Kang, 2012 ; Hishikawa et al, 2017 ). The concentration of ω-3 fatty acids in glycerophospholipids was obviously elevated in EEOS group mice than in model group, which is consistent with found that ω-3 fatty acids were significantly upper in normal people compared to patients with uronephrolithiasis ( Bikulčienė et al, 2018 ), indicating that EEOS extract may reduce the occurrence of kidney stones by regulating the ω-3 fatty acids metabolism.…”
Section: Discussionsupporting
confidence: 88%
“…Fatty acids metabolism is closely related to the formation of kidney stones ( Takahiro et al, 2008 ; Hall et al, 2017 ; Bikulčienė et al, 2018 ). Esterified fatty acids in glycerophospholipids are potential precursor for lipid mediators, especially ω-3 fatty acids ( Kang, 2012 ; Hishikawa et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The FTIR results of the studies [80,81] demonstrated that there were several alterations in the triglyceride spectral region of SAT and VAT of male obese mice. The authors [82] have used FTIR spectroscopy to investigate the composition of fatty acid of adipose tissue in men having the metabolic syndrome. The results from the patients with uronephrolithiasis differed from the results from the control group.…”
Section: Ftir and Raman Spectroscopiesmentioning
confidence: 99%